FEATURES 2D AND 3D/4D ULTRASONIC DIAGNOSTICS OF DEVELOPMENTAL ANOMALIES OF THE FACE AT A FETUS IN II AND III TRIMESTER - S. M. Voevodin; T. V. Shemanaeva (IRBIS LLC, 2016)
For the purpose of finding-out of possibilities of multiplane receptions and 3D/4D echographies in prenatal diagnostics of anomalies of development of the face at a fetus in II and III trimester are analyzed 131 case of successful diagnostics of such defects at 109 pregnant women. The gestational age at the moment of primary revealing has made 14-40 weeks. It is established that in the presence of hiatuses of the top jaw, also other developmental anomalies of the face use 3D/4D echographies especially in IIth trimester considerably facilitates diagnostics, thanks to reception of larger number of evident planes of scanning. The estimation of facial structures in the end of IIIth trimester of pregnancy can be inconvenient.